Studying nursing using problem-based and enquiry-based learning - Price, Bob (Palgrave Macmillan, 2003)
This title provides students with information and guidance in understanding the theory and processes of problem-based learning/enquiry based learning within health care contexts. It provides a succinct, accessible summary of theory, before guiding the reader through the stages of an inquiry, using illustrations and case studies to help the reader gather and analyse information. Featuring wide-ranging "how to" examples drawn from different fields of nursing, this text gives the student advice on practice observation, interviews, library searches and using the internet. It should be a useful study guide for all pre- and post-qualifying nurses using PBL/EBL.